A Collective Statistical Analysis of Outdoor Path Loss Models - Abdullah, Saifuddin; Al-Najjar, Dr. Fuad (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
This study encompasses nine path loss models (Erceg-Greenstein, Green-Obaidat, COST Hata, Hata Urban, Hata Rural, Hata Suburban, SUI, Egli and ECC-33) which were programmed on Python and studied for their results in an urban architecture (translated by higher attenuation variables) at 950 MHz and 1800 MHz. The results obtained showed that increasing the transmission antenna height with the increasing distance not only lowers down the path loss readings, but also shows that the standard deviation between the results of studied path loss models increases with the increasing transmission antenna height and increasing distance at both 950 MHz and 1800 MHz systems, especially when transmission antenna height crosses the GSM standard of 40 meters and cell-radius exceeds the limit of 20 kilometers. Moreover, it is also observed that at both 950 MHz and 1800 MHz, the path loss readings of all the models disperse from their collective mean between 1 and 10 Km, but tend converge afterwards (i.e. from 10 to 40 Km and onwards) towards their mean, which indicates that path loss readings of the urban models tend to follow either a single convergence point on large distances or reach their maximum threshold level (a level from which their readings cannot exceed or differ from each other significantly).